Matching schemes and public goods: A review - Raphael Epperson; Christiane Reif (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2018)
Matching schemes, where a party matches the contribution of others, reduce the effective price of a good and aim to foster its demand. We review the empirical literature on the effectiveness of these schemes in the context of public goods, especially in the field of charitable giving. As different measures of effectiveness are used, we classify results according to (i) the level of public good provision, (ii) the amount of individuals' contributions, (iii) the likelihood to give and (iv) the contribution conditional on contributing a positive amount. Generalizing results is challenging, since context specific factors matter. Predominantly, a match is found to create a significant increase in public good provision without crowding out individuals' contributions, while the effect on the likelihood of giving and contribution condition on contributing a positive amount is nonnegative. The discussion reveals several avenues for future research, as putting stronger emphasizes on long term effects, public good competition or heterogeneity in responses.
Keywords: D01; D64; H41; L31; 330; literature review; matching schemes; charitable giving; public goods